Changes in tree species diversity, composition and aboveground biomass in areas of fuelwood harvesting in miombo woodland ecosystems of southern Malawi. Issue 3 (3rd July 2019) - Nerfa, Lauren; Rhemtulla, Jeanine M.
ABSTRACT: Fuelwood is an essential forest product for small-holder farmers in the tropics, but fuelwood harvesting may cause forest degradation and impact ecosystem services. Understanding tree species composition, diversity and biomass changes in forests with active fuelwood collection is important for informing sustainable forest harvesting. In the miombo woodlands of southern Malawi, using forest plots, we investigated: 1) if forests with fuelwood harvesting (n = 50) have different tree, sapling and seedling stem density, species diversity, species composition, and aboveground biomass (AGB) than forests with minimal use (n = 36); and 2) if forest product harvesting pressure and access are predictors of tree stem density, diversity and AGB. We found a significant reduction in tree diversity and AGB but not stem density, and different species composition in areas with fuelwood harvesting compared to reference sites. For saplings, stem density was higher and species composition was different in fuelwood harvesting sites. Seedling Shannon index and Simpson's diversity were lower in fuelwood harvesting sites. Harvesting pressure and access were predictors of AGB and tree stem density. The reduced AGB and tree species diversity may hinder collection of fuelwood and other forest products, and may reduce ecosystem functioning. Exploring the possibility of forest landscape restoration in the area could be beneficial.